URGENSI PENGAKUAN PERLINDUNGAN HUKUM KEPADA KORBAN NON DEBITUR DALAM PENAGIHAN PINJAMAN ONLINE - Kemalasari, Ni Putu Yuliana (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2025)
The massive development of online loans in society not only makes it easier for people to get loans, but also raises new legal problems. Theproblem is related to the billing process which is sometimes carried out unethically. Unethical online loan billing is not only directed at the debtordirectly but also against third parties (non-debtors) who have no relationship at all with online loan transactions. Non-debtor victims are generally family members, co-workers, or people whose contacts are randomly stored in the debtor's phone contactswhose personal data is accessed and misused without consent. This article examines the urgency of recognizing legal protection for non-debtorvictims who experience violence in unethical online loan collection. The main problem to be studied is how there is no recognition of the legalstatus of non-debtor victims in online loan collection regulations, and how effective legal protection efforts are to provide legal protection to non-debtor victims. The research method used is a normative juridical method using a legislative approach. The results of the study show that the current regulationshave not given a position to non-debutur victims as legal subjects who must be protected in online loan collection. Therefore, a legalreformulation is needed to provide explicit recognition of non-debtor victims as part of human rights to obtain legal protection for various actsthat are contrary to human rights. Keywords: Non-Debtor Victims; Online Loans; Debt Collection; Legal Protection; Personal Data.